Atriplex retusa, the correct name for A. deserticola (Chenopodiaceae; Amaranthaceae sensu APG) - Böhnert, Tim; Luebert, Federico; Weigend, Maximilian (Phytotaxa, 2018)
The genus Atriplex Linnaeus (1753: 1052) (Chenopodiaceae Vent.; placed in Amaranthaceae Juss. s. l. in APG IV 2016) comprises about 300 species distributed mainly in subtropical, temperate, and subarctic regions of the world and is mostly adapted to dry conditions on often saline soils (Sukhorukov & Danin 2009, Kadereit et al. 2010, Iamonico 2013, APG IV 2016). The genus is highly diverse in Eurasia, Australia and North America. South America is another centre of diversity with ca. 55 species, 45 of which are considered as native (Brignone et al. 2016). A recent and exhaustive taxonomical synopsis of Atriplex for South America was published by Brignone et al. (2016), but there are also regional taxonomic revisions, e.g., for Chile by Rosas (1989), or Argentina by Múlgura de Romero (1981, 1982 & 1984).